Evolution to Digital Government through Intelligent Government in Korea - Cho, June-Suh (Archives of Business Research, 2021)
The Fourth Industrial Revolution can be summarized as the evolution of a connected and more intelligent society. Moreover, intelligence information technology is the driving force of change as the industry’s fundamental structural changes. The intelligence government is one of the digital governments that the Korean e-Government aims for. Korea is one of the leading e-government countries in the world. It is responsible for leading and disseminating e-government around the world, especially in the developing world. In this paper, we discuss the stages of change, strategies, efforts, and examples from the Korean e-government to intelligent government, present guidelines, and discuss future development directions.